Study on the influence of confining pressure and unloading damage on the bursting liability characteristics of coal - Du, Taotao; Pan, Junfeng; Xia, Yongxue; Sun, Ruda (Frontiers in Earth Science, 2023)
The research on the bursting liability of coal under confining pressure and unloading damage is critical in creating prevention mechanisms for coal mass rock bursts in deep underground mines. Cyclic loading and unloading tests of variable stress with a lower limit were performed under multistage confining pressure and different amplitude unloading to explore their influence on the impact tendency of the coal bodies. Meanwhile, the characteristic parameter analysis of acoustic emissions was used to evaluate the failure. The results revealed that the accumulated number and energy of acoustic emission events gradually decreased with increasing the confining pressure. The coal specimen became denser, and the failure mode gradually transitioned from brittle to ductile. With the increase in unloading amplitude, the cumulative number of acoustic emission events in the coal specimens decreases, the damage degree to the coal body increases, the peak load decreases, and the failure mode transitions from ductile to brittle. The increase in confining pressure results in an increase in the input energy and the elastic strain energy, while the increase in the unloading range of the coal body leads to a decrease in the input energy and elastic strain energy. In addition, after the confining pressures of 3 MPa, 6 MPa, and 9 MPa, the residual elastic energy index of the coal specimens increases by 21.76%, 42.92%, and 71.69%, respectively, compared with the room pressure conditions. The residual elastic energy index decreases by 21.11% and 55.38% for the unloading amplitude of 3 MPa and 6 MPa, respectively, compared with the unloaded coal specimen, indicating that the impact tendency of the coal body is enhanced by the confining pressure conditions.